Comparative Analysis of the Approaches of Imam al-Bayhaqi and Ibn Rajab al-Hanbali in Taʿlil al-Hadith Through the Use of Shawahid and Mutabi‘at to Mu‘allal Hadith - Akhmad Ilham Samudera; Ahmad Wildan; Rizzaldy Satria Wiwaha; Rezza Pahlevi Dalimunthe; Dadah Dadah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze and compare the taʿlil al-hadith methods between Imam al-Bayhaqi and Ibn Rajab al-Hanbali, two important figures in the classical tradition of hadith criticism who represent two different methodological styles. Al-Bayhaqi is known for his jamʿwa taqwiyah approach which emphasizes the strengthening of hadith through shawahid and mutabiʿat, while Ibn Rajab stands out with his tamyiz wa tahqiq style which focuses on identifying the hidden ‘illah in the sanad. This study uses a qualitative method with a descriptive-comparative approach to primary sources, namely al-Bayhaqi’s works such as as-Sunan al-Kubra and al-Madkhal ila as-Sunan al-Kubra, as well as Ibn Rajab’s works such as Sharh ʿIlal al-Tirmidhi and Jamiʿ al-ʿUlum wa al-Hikam. The results of this study indicate that although both have different epistemological orientations, both strive to maintain the authenticity of the hadith by balancing strengthening the sanad and exposing hidden flaws. This finding contributes to the enrichment of modern hadith criticism methodology by emphasizing the importance of integrating a textual approach with in-depth sanad analysis.